Developing a dynamic visualization of the Oracle Query Execution Process - Yost, Andrew (My University, 2007)
The complexity of the Oracle database management system (DBMS) query execution process in addition to the lack of available resources detailing the process have historically made teaching the process quite difficult. In response to this difficulty members of our group had developed an application to visually simulate the execution process for certain SQL statements executed against an Oracle DBMS. As an extension to this project we have expanded the previous simulator to include functionality for dynamic SQL interaction with an instance of the Oracle DBMS. By extending previous design patterns as well as incorporating a facade design pattern for data access, the simulator was redesigned to retain the static execution functionality existing previously, but also to provide new dynamic query submission and visualization capabilities. By interacting with an Oracle DBMS instance through Java Database Connectivity, the simulator provides a visual representation of the execution process for user-generated queries within a specific oracle DBMS environment. We have also incorporated the ability for the simulator to extract and display the execution plan developed during the query execution process. These capabilities allow the simulator to visualize both the execution of a broad range of queries as well as changes in the DMS environment.
Color poster with text describing research conducted by Andrew Yost advised by Paul J. Wagner.
Keywords: Oracle (Computer file); SQL/ORACLE (Computer program language); Database management; Relational databases; Computer simulation; Java (Computer program language); Application program interfaces (Computer software); Posters